Using Mac OS X Lion - Johnson, Yvonne (Using--, 2012)
Don't just read about Mac OS X Lion: See it and hear it with step-by-step video tutorials and valuable audio sidebars delivered through the free Web Edition that comes with every USING book. For the price of the book, you get online access anywhere with a web connection - no books to carry, content is updated as Mac OS X Lion changes, and the benefit of video and audio learning. Way more than just a book, this is all the help you'll ever need where you want, when you want! INCLUDES MORE THAN 3 HOURS OF FREE VIDEO & AUDIO Show Me video walks through tasks you've just got to see Tell Me More audio delivers insights straight from the experts 2 CONVENIENT WAYS TO ACCESS THE VIDEO TUTORIALS AND AUDIO SIDEBARS The 69 media files are available on the included DVD. The Web Edition of USING Mac OS X Lion, which includes the media files, is available online anytime and anywhere once you've registered your book at quepublishing.com/using.